2020
DOI: 10.1101/2020.05.29.123216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telomere length is highly heritable and independent of growth rate manipulated by temperature in field crickets

Abstract: Many organisms are capable of growing faster than they do. Restrained growth rate has functionally been explained by negative effects on lifespan of accelerated growth. However, the underlying mechanisms remain elusive. Telomere attrition has been proposed as a causal agent and has been studied in endothermic vertebrates. We established that telomeres exist as chromosomal-ends in a model insect, the field cricket, using terminal restriction fragment and Bal 31 methods. Telomeres comprised TTAGGn repeats of 38k… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…TL evolvability was also low in field crickets (Boonekamp et al, 2020a), which fits the expectations for a trait related to fitness (Houle et al 1992), where high selection pressures and trait canalisation are expected (Stearns, Kaiser, & Kawecki, 1995;Vedder, Verhulst, Bauch, & Bouwhuis, 2018). But more studies that provide coefficients of additive genetic variation for comparison among populations and taxa are required to gain a more comprehensive picture.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…TL evolvability was also low in field crickets (Boonekamp et al, 2020a), which fits the expectations for a trait related to fitness (Houle et al 1992), where high selection pressures and trait canalisation are expected (Stearns, Kaiser, & Kawecki, 1995;Vedder, Verhulst, Bauch, & Bouwhuis, 2018). But more studies that provide coefficients of additive genetic variation for comparison among populations and taxa are required to gain a more comprehensive picture.…”
Section: Discussionsupporting
confidence: 74%
“…The evolutionary potential of a trait is dependent on the additive genetic variance, which scaled to the mean of the trait yields a metric known as the evolvability (Houle, 1992). We are aware of one study estimating the evolvability of TL, in an insect, which found evolvability to be low despite high heritability (Boonekamp et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has been shown to effect within individual changes in DNAm (Sheldon et al, 2020) and telomere length (Stier et al 2020;Fitzpatrick et al 2019) however, it is unclear if temperature effects these DNA modifications comparably. The temperatures (average daily maximum of 27.6 o C) in our study may not have been 'stressful' enough to impact telomere dynamics, and indeed temperature has not affected telomere length in studies on other taxa (McLennan et al, 2018;Boonekamp et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…Previous work (Boonekamp et al, 2020) identified significant heritability of growth rate, again using nymphs reared in sibling groups. In our growth rate study, nymphs were reared individually to eliminate environmental effects resulting from competition (including faster growing individuals potentially having to compete with faster growing siblings).…”
Section: Discussionmentioning
confidence: 96%
“…Lastly, we investigated whether in addition to the observed genetic variation in growth rate (G × Age), there was also evidence for genetic variation in the response to temperature (G × E) as such effects were reported in a similar experiment (Boonekamp et al, 2020). However, the bivariate model (with body mass at the two temperature conditions after 39 days of treatment as the response variables) yielded unreliable results due to singularities and/ or estimates that were highly dependent on initial starting values of the ASReml optimization procedures.…”
Section: Growth Ratementioning
confidence: 98%